Serum Inhibin Concentration in Dogs with Adrenal Gland Disease and in Healthy Dogs. (11th January 2013) - Brömel, C.; Nelson, R.W.; Feldman, E.C.; Munro, C.J.; Kass, P.H.; Vico, A.E.; Labelle, P.; Conley, A.J.
<x xml:space="preserve">Abstract</x> Background Studies in humans identified the synthesis and secretion of inhibin from adrenocortical tumors, but not pheochromocytoma (PHEO). Inhibin has not been examined in dogs as a serum biomarker for adrenal gland tumors. Objective To determine serum inhibin concentration in dogs with adrenal gland disease and in healthy dogs. Animals Forty‐eight neutered dogs with adrenal disease including pituitary‐dependent hyperadrenocorticism (PDH, 17), adrenocortical tumor (18), and PHEO (13), and 41 healthy intact or neutered dogs. Methods Prospective observational study. Dogs were diagnosed with PDH, adrenocortical tumor (hyperadrenocorticism or noncortisol secreting), or PHEO based on clinical signs, endocrine function tests, abdominal ultrasound examination, and histopathology. Inhibin concentration was measured by radioimmunoassay in serum before and after ACTH stimulation, and before and after treatment. Results In neutered dogs, median inhibin concentration was significantly higher in dogs with adrenocortical tumors (0.82 ng/mL) and PDH (0.16 ng/mL) than in dogs with PHEO and healthy dogs (both undetectable). Median inhibin concentration was significantly higher in dogs with adrenocortical tumors than in those with PDH and decreased after adrenalectomy. Median inhibin concentration was significantly higher in intact than in neutered healthy dogs and was similar in pre‐ and post‐ACTH stimulation. Sensitivity, specificity, and accuracy of serum inhibin concentration for identifying an adrenal tumor as a PHEO were 100, 88.9, and 93.6%, respectively. Conclusions and Clinical Importance Adrenocortical tumors and PDH but not PHEOs are associated with increased serum inhibin concentration; undetectable inhibin is highly supportive of PHEO in neutered dogs with adrenal tumors.